Biodiversity of Malaysian mangrove fungi and phylogeography of Verruculina enalia from selected Southeast Asian countries / Siti Sarah Sharuddin - Sharuddin, Siti Sarah (2012)
Mangroves are important to the ecosystem as it protects the coastline from erosion, act as a nursery ground for the young sea life creatures and become a habitat for many organisms including hundreds of species of birds (both migratory and resident),monkeys, and lizards. Mangroves also provide a wide variety of substrates for fungi to grow. However, this study will focus on the lignocellulosic material only. Biodiversity of lignicolous mangrove fungi were sampled from three study sites of the Peninsular Malaysia mangrove forest. Cape Rachado (a sandy mangrove forest dominated by Rhizophora apiculata), Telok Pelandok (rocky shores with sandy mangroves dominated by Avicennia spp.) and Morib (a muddy mangrove forest dominated by Rhizophora spp.). Five hundred thirty six samples collected yielded 136 fungal taxa which comprises of 105 Ascomycota, 29 anamorphic fungi and 2 Basidiomycota. The most common (>10%) marine fungi from this study were Dactylospora haliotrepha, Haloresellinia oceanica and Kallichroma tethys which occurred in all 3 study sites. Species diversity was greatest in Telok Pelandok with 71 species recorded followed by Cape Rachado with 69. However, Cape Rachado has the highest Shannon-Weiner diversity index when evenness and total number of species occurrence were taken into account. Fungal species recorded showed little habitat recurrence as Sørensen similarity indices for all sites are below 0.5. There are no phylogeography study done on marine fungi to date even though several terrestrial mycota have been examined with most of the studies on geographical differences of fungi are done on the terrestrial Basidiomycota. This is the first initiative study on investigating the phylogeography of marine fungi. Verruculina enalia, a marine mangrove fungus was chosen as the case study. The genetic relationship and variations of V. enalia from various biogeographical isolates was studied. The isolates of V. enalia are taken from Malaysia, Philippines, Hong Kong and Taiwan. One ITS iv sequence of V. enalia isolated from Liberia deposited in GenBank was also included in the analysis. DNA sequence variation in nuclear ITS was examined to measure any genetic divergence among the isolates from different localities. Based on the phylogenetic analysis, isolates from Malaysia, Hong Kong, Philippines and Singapore are similar in terms of its sequences while isolates from Jici Rocky shore, Taiwan are different from the others to form a separate clade but differ for only less than 1%. V. enalia might possibly have not evolved long enough to accumulate mutations. Despite a strong bias toward sampling sites in the Southeast Asia region, this might be a signal that genetic variation among similar species that comes from the same ocean basin is minimal or does not have any variation at all which makes them totally identical. However, more isolates from wider geographical locations are required to confirm this.